The power of color (Owatonna, MN Learning Zone Express, 2002)
Discusses the basic principles of color and provides tips for choosing and combining colors for fashion and interior design.
DVD
Printable teaching materials available online at www.learningzoneexpress.com/worksheets.
Originally produced in 2000.
Camera, Tom Adair, Lori Casey ; audio, John Dehn ; music, Chan Poling Music.
A brief history of color.
What is color?
Keywords: Color; Color -- Psychological aspects; Color in interior decoration